Demonstration on serum bilirubin estimation - Kuttulebbai Naina Mohamed Salam, Sirajudeen; Mat Harun, Noraihan; Mohd Noor, Mohd Fadly; Abdullah, Nor Zamzila (2021)
In this video, we describe the objective of serum bilirubin estimation, the procedure and clinical interpretation of the results